EFFECTIVENESS OF “PIK-R” PROGRAM AS AN EXTRACURRICULAR FOR HIGH/VOCATIONAL SCHOOL STUDENTS IN PREVENTING NEGATIVE BEHAVIORS OF ADOLESCENTS - Dwi Hastuti; Alfiasari Alfiasari; Neti Hernawati; Oktriyanto Oktriyanto; Mardiana Dwi Puspitasari (Jurnal Cakrawala Pendidikan, 2019)
PIK-R (Pusat Informasi Konseling Remaja) as one of the programs for adolescents is expected to be able to contribute positively in developing positive behavior and suppress the potential for negative adolescent behavior. This study aims to analyze the positive and negative behavior of high/vocational school students and their relation to knowledge, participation, and effectiveness of the PIK-R program at school. This study used a cross sectional study design involving 687 students in selected public and private high/vocational schools in Bekasi City, Indonesia. Structured questionnaire is used to measure the students’ characteristics, the students’ negative behavior, and the effectiveness of the PIK-R program. The study found that only 54.88% of students were aware of the PIK-R program and only 8.11% attended the program. Even so, the results of different tests show that students who take part in the PIK-R program show significantly lower negative behaviors, especially in pornography, online games, and smoking addiction. In addition, it was also found that male students tended to have higher negative behavior than female students. The results of multiple linear regression also show the real effect of the PIK-R program in suppressing the negative behaviors of adolescents.